Contribucion al conocimiento de la Ortopterocenosis de la Peninsula Iberica - Coca Abia, M.=700 1 Quero Lopez, C.; Sopeña Mañas, J.M.; Martin Bernal, E.
(Es, En)
Ilus., 10 ref.
Keywords: ORTOPTERA; ACRIDIDAE; CALLIPTAMUS; DOCIOSTAURUS; INSECTA; PLAGAS DE PLANTAS; ESPAÑA